A Coumarin-Based Fluorescent Probe for Ratiometric Detection of Cu2+ and Its Application in Bioimaging - Zhang, Jie; Chen, Meng-Yu; Bai, Cui-Bing; Qiao, Rui; Wei, Biao; Zhang, Lin; Li, Rui-Qian; Qu, Chang-Qing (Frontiers in Chemistry, 2020)
The fluorescent probe L based on naphthalimide-modified coumarin was designed, synthesized and characterized, which could recognize Cu2+ from other cations selectively and sensitively in HEPES buffer (10 mM, pH=7.4)/CH3CN (1:4, V/V). When the probe L interacted with Cu2+, the color and the fluorescent intensity changed obviously. And it provided the naked-eye detection for Cu2+. The recognition mode between them was achieved by Job's plot, IR, MS, SEM and 1HNMR. In addition, test strips made from L could still interact with Cu2+ in tap water effectively. The limit of detection (LOD) of L was 3.5 × 10−6 M. Additionally, Density Functional Theory (DFT) calculation method was used to analyze the action mechanism of L toward Cu2+. Importantly, the fluorescent probe L could demonstrate the favorable selectivity toward Cu2+ in Caenorhabditis elegans. Thus, L was considered to have some potential for application in bioimaging.